Isolated Tibial Component Failure in Total Knee Arthroplasty: A Case Series Evaluating Inflammatory Response versus Mechanical Failure - Yokhana, Sanar S.; Bergum, Christopher; Ren, Weiping; Markel, David C. (The Journal of Knee Surgery, 2019)
Total knee prostheses are routinely redesigned to improve performance, longevity, and to closer mimic the native kinematics of the knee. Despite continued improvements, all knee implants, even those with proven design features, have failures. We identified a cohort of patients with isolated tibial component failures that occurred in a popular and successful knee system. Our purpose was to (1) characterize the observed radiographic failure pattern; (2) investigate the biologic response that may have contributed to the failure; and (3) to determine if the failure mechanism was of a biological or a mechanical nature. Twenty-one knees from 19 patients met the inclusion criteria of isolated tibial component failure in a single knee implant system. Radiographs from the primary and revision knee surgery were analyzed for implant positioning and the failure pattern. Inflammatory biomarkers interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α were available in 16/21 knees and peripheral CD14+/16+ monocytes were measured in 14 of the aforementioned 16 knee revisions. Serum CD3, CD4, and CD19 were measured in 10 of the aforementioned 14 knees. Additionally, white blood cell (WBC) count, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) were measured to rule out infection as a cause of the cytokine upregulation. Radiographic findings demonstrated that all of the 21 tibial components were implanted in either neutral or 2 to 3 degrees varus in the coronal plane, and none of the revisions was implanted in valgus. All tibias showed obvious radiographic loosening and the implant failed into varus. The inflammatory biomarkers IL-1β, IL-6, and TNF-α were negative. WBC, ESR, and CRP were normal. Serum CD3, CD4, and CD19 flow cytometry analyses were found to be in the normal range. Peripheral CD14+/16+ and total CD16+ monocytes measurements were consistent with previous findings of patients with osteoarthritis, rather than particulate-induced inflammatory loosening. The findings support the implant failure observed in our study occurred by a different mechanism than the wear debris–induced aseptic loosening. We believe that a mechanical failure can occur based on our findings. The loosening, collapse, and debonding from the cement may have been related to the implantation technique, stresses due to favorable rotational freedoms of the implant, or patient characteristics/behavior. Continued exploration into implant failure mechanisms and particularly into the biologic response associated with failure is ongoing.
Keywords: total knee arthroplasty; Scorpio knee; revision knee arthroplasty; implant failure